Advocacy of targeting protease‐activated receptors in severe coronavirus disease 2019. (7th July 2021) - Subramaniam, Saravanan; Ruf, Wolfram; Bosmann, Markus
Abstract : Identifying drug targets mitigating vascular dysfunction, thrombo‐inflammation and thromboembolic complications in COVID‐19 is essential. COVID‐19 coagulopathy differs from sepsis coagulopathy. Factors that drive severe lung pathology and coagulation abnormalities in COVID‐19 are not understood. Protein–protein interaction studies indicate that the tagged viral bait protein ORF9c directly interacts with PAR2, which modulates host cell IFN and inflammatory cytokines. In addition to direct interaction of SARS‐CoV‐2 viral protein with PARs, we speculate that activation of PAR by proteases plays a role in COVID‐19‐induced hyperinflammation. In COVID‐19‐associated coagulopathy elevated levels of activated coagulation proteases may cleave PARs in association with TMPRSS2. PARs activation enhances the release of cytokines, chemokines and tissue factor expression to propagate IFN‐dependent inflammation, leukocyte‐endothelial interaction, vascular permeability and coagulation responses. This hypothesis, corroborated by in vitro findings and emerging clinical evidence, will focus targeted studies of PAR1/2 blockers as adjuvant drugs against cytokine release syndrome and COVID‐19‐associated coagulopathy. LINKED ARTICLES: This article is part of a themed issue on The second wave: are we any closer to efficacious pharmacotherapy for COVID 19? (BJP 75th Anniversary). To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v179.10/issuetoc